An Active-Clamp Forward Inverter Featuring Soft Switching and Electrical Isolation - Chien-Hsuan Chang; Chun-An Cheng; Hung-Liang Cheng; Yen-Ting Wu (Applied Sciences, 2020)
Traditional photovoltaic (PV) grid-connection inverters with sinusoidal pulse-width modulation (SPWM) control suffer the problem of buck-typed conversion. Additional line-frequency transformers or boost converters are required to step-up output voltage, leading to low system efficiency and high circuit complexity. Therefore, many flyback inverters with electrical isolation have been proposed by adopting a flyback converter to generate a rectified sine wave, and then connecting with a bridge unfolder to control polarity. However, all energy of a flyback inverter must be temporarily stored in the magnetizing inductor of transformer so that the efficiency and the out power are limited. This paper presents a high-efficiency active-clamp forward inverter with the features of zero-voltage switching (ZVS) and electrical isolation. The proposed inverter circuit is formed by adopting a forward converter to generate a rectified sine wave, and combining with the active-clamp circuit to reset the residual magnetic flux of the transformer. Due to the boost capability of the transformer, this inverter is suitable for the PV grid-connection power systems with wide input-voltage variation. The operation principles at steady-state are analyzed, and the mathematical equations for circuit design are conducted. Finally, a laboratory prototype is built as an illustration example according to proper analysis and design. Based on the experimental results, the feasibility and satisfactory performance of the proposed inverter circuit are verified.